MATHEMATICS IN EDUCATIONAL PLAYFUL PRACTICES IN THE TEACHING-LEARNING PROCESS OF CHILDREN IN THE EARLY YEARS IN ELEMENTARY SCHOOL - Joana Nély Marques Bispo (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
This article aims to report the ludic educational practices of a teacher carried out with children in the early years of Elementary School in a public school in the city of Niterói, in the state of Rio de Janeiro; highlighting the subject Mathematics developed in an interdisciplinary and transdisciplinary way. This report exposes the possibilities of the teaching-learning process under the methodology in/of/with the everyday authored by Nilda Alves (2002, 2007, 2008 and 2015). To delineate the educational ludic actions, narratives of children in the 4th year of schooling, images and descriptions of each activity will be used. The results refer to the positive aspects of a playful pedagogy with the fraction in cooking, for this an arugula pizza was made in the school cafeteria, money from the grocery store was used, we also used the multiplication board, as well as a video of indigenous culture and the study of flat geometric figures through Brazilian indigenous graphics; exemplifying that it is possible to transform classes into moments of remarkable experiences.